THE STUDY OF INCORRECT USAGE OF THE WORD “APOTEK” IN PROPER AND CORRECT INDONESIAN - Ertinawati, Yuni; Nugroho, Gilang Setyo; Zakia, Salwa; Nurulfadilah, Syahla Maulida (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The purpose of this study is to analyze the use of the word “apotek” on shop signboards. A shop signboard shows the name of the shop and helps visitors find its location. If there are mistakes in writing words on the signboard, the content of the signboard will not be clear or precise if the words are written incorrectly. This sample was taken in the Tasikmalaya City area. The method used in this research is a descriptive method which is qualitative in nature. The data collection techniques used are direct observation, documentation, and analysis. Through these techniques, this study identifies the use of the word “apotek” which does not following ethics in language, and the Enhanced Spelling (EYD) and the Big Indonesian Dictionary (KBBI). The results of this study show that there are still many signboards that write the word “paotek” incorrectly. Errors in the use of these words are caused by the influence of colloquial use and limited knowledge in the rules of Indonesian language use. In addition, the problem of language errors in writing signboards can arise because people pay less attention to the use of proper language when writing.